KAJIAN NILAI BUDAYA PADA TARI BEDAYOU TULANG BAWANG - Rifki Ayu Rosmita (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to examine the cultural values in the Bedayou Tulang Bawang dance. The Bedayou Tulang Bawang dance was analyzed using ethnochoreologi theory assisted by folklore theory. The method used in this research is qualitative method. Data collection techniques were carried out by means of observation, interviews, and documentation studies. To analyze the cultural value in the Bedayou Tulang Bawang dance, the researchers used data reduction, data presentation, and drawing conclusions. The analysis produces cultural values, namely the value of self-confidence and nemui nyimah (friendly, polite, and tolerant).